2004
DOI: 10.1105/tpc.104.023150
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics of the Arabidopsis Plasma Membrane and a New Phosphorylation Site Database[W]

Abstract: Functional genomic technologies are generating vast amounts of data describing the presence of transcripts or proteins in plant cells. Together with classical genetics, these approaches broaden our understanding of the gene products required for specific responses. Looking to the future, the focus of research must shift to the dynamic aspects of biology: molecular mechanisms of function and regulation. Phosphorylation is a key regulatory factor in all aspects of plant biology; but it is difficult, if not impos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
409
4
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 455 publications
(448 citation statements)
references
References 69 publications
31
409
4
4
Order By: Relevance
“…ABC transporters have been shown to require phosphorylation for activity or regulation (Kolling, 2002). A recent study of phosphorylated plasma membrane proteins identified PEN3 as a target of flagellin-induced phosphorylation (Nü hse et al, 2004), supporting the idea that PEN3 functions in nonhost resistance and defenses elicited by nonspecific elicitors such as flagellin. Consistent with this idea, PEN3 expression was 2.5-fold higher in flg22 peptide-treated seedlings compared with control seedlings, and this induction was dependent on the FLS2 receptor-like kinase (see Supplemental Table 2 online) (Gomez-Gomez and Boller, 2000).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…ABC transporters have been shown to require phosphorylation for activity or regulation (Kolling, 2002). A recent study of phosphorylated plasma membrane proteins identified PEN3 as a target of flagellin-induced phosphorylation (Nü hse et al, 2004), supporting the idea that PEN3 functions in nonhost resistance and defenses elicited by nonspecific elicitors such as flagellin. Consistent with this idea, PEN3 expression was 2.5-fold higher in flg22 peptide-treated seedlings compared with control seedlings, and this induction was dependent on the FLS2 receptor-like kinase (see Supplemental Table 2 online) (Gomez-Gomez and Boller, 2000).…”
Section: Discussionmentioning
confidence: 81%
“…Recently, proteomic studies of different organelles have placed PEN3 in the plasma membrane, mitochondria, and chloroplasts (Brugiere et al, 2004;Kleffmann et al, 2004;Nü hse et al, 2004). Given its high abundance, PEN3 is likely a common contaminant in organelle preparations and unlikely to be localized in all three subcellular structures.…”
Section: Localization Of Pen3 To Penetration Sites After Pathogen Attackmentioning
confidence: 99%
“…In this context, ALA10 could also function as a sensor of phospholipids in the soil environment that initiates signalling events leading to secretion of phosphatases. Like transceptors 32,33 , ALA10 is subject to phosphorylation in planta at serine and threonine residues 20,21 , which suggests that it is subject to tight regulation. One of the first signs of phosphate starvation in A. thaliana is that the root enters a determinate developmental programme in which primary root growth is arrested and cell differentiation is promoted, thereby stimulating lateral root growth and increasing the root surface area 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale proteomic studies suggest that ALA10 exists as a phosphoprotein at the plasma membrane 20,21 . In animal cells, P4-ATPases at this location constantly remove PS from the outer plasma membrane leaflet, which protects cells, as macrophages engulf cells with this phospholipid exposed at their surface 22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation